System of lexical nomination in author’s discourse - Mykytiuk, I. M.; Микитюк, Ірина Михайлівна; Микитюк, І. М. (Одеса, 2017)
У статті розглянуто систему лексичної номінації в авторському дискурсі австралійського письменника А.Б. Патерсона. Номінативний простір дискурсу А.Б. Патерсона характеризується використанням одиниць номінації, які належать до таких тематичних груп: людські істоти, фауна, предмети щоденного вжитку, рукотворні та природні об’єкти, флора.

The article explores the system of lexical nomination in the author’s discourse of Australian writer A.B. “Banjo" Paterson. Nom¬inative dimension of A.B. “Banjo" Paterson’s discourse is characterized by the usage of nomination units that belong to such thematic groups: nominations of human beings, nominations of fauna, nominations of objects of everyday life, nominations of manmade and natural objects, nominations of floristic objects.
Mykytiuk I. M. System of lexical nomination in author’s discourse / I. M. Mykytiuk // Одеський лінгвістичний вісник. – 2017. – Вип. 9. – Т.1. – С. 147-151.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; номінація; авторський дискурс; тематична група; nomination; author’s discourse; thematic group